Synthesis and Characterization of Polydimethylsiloxane end-Modified Polystyrene from Poly(Styrene ¿ co ¿Vinyltriethoxysilane) Copolymers (2016)
ABSTRACT: In this paper, we report the synthesis of polystyrene end- capped with three- short- arm PDMS (PS-(PDMS)3 ) using poly(styrene – co –vinyltriethoxysilane) copolymers as precursors. These materials were obtained in a two-step process; first, two random copolymers of poly(St – co – VTES) having different molecular weight, and vinyltriethoxysilane content were prepared via free radical polymerization. The materials thus obtained, were treated with an excess of dimethyldimethoxysilane to produce PS-(PDMS)3 by co-condensation of alkoxysilane groups. The formation of the copolymers was confirmed by proton nuclear magnetic resonance, infrared spectroscopy, and gel permeation chromatography. Surface properties of films formed by casting the copolymers on a glass sheet were studied by Atomic force microscopy (AFM), and water contact angle measurements. We found that PS-(PDMS)3 copolymers exhibit a hydrophobic behavior, showing water contact angles close to values early reported for block copolymers composed by PS and PDMS segments, and comparable with the corresponding value of PDMS.